PENGUATAN KARAKTER KEBANGSAAN DAN PEMBERDAYAAN MASYARAKAT TIYUH TIRTA MAKMAUR - Budhi Martana; Sugianto Sugianto; Suyanti Suyanti (LPPM UPN Veteran Jakarta, 2018)
The purpose of this activity is to foster the motivation of people in the region to actively participate indevelopment through opportunities and life experiences to socialize with communities of different regions, so as tofoster a spirit of tolerance with a deep understanding of the values and diversity of Indonesian culture. The targetsand outcomes expected from this program are (1) able to work together in formulating their potential through theapplication of science and technology, (2) being able to design work programs and apply them responsibly, (3)being able to manage changes in themselves and the environment, communicate and motivate groups andcommunities, and (4) have strong, honest, caring and respectful personalities. The method of implementingNationalism KKN activities is carried out in the form of socialization / counseling and trainings involving thegovernment and the community directly. The results achieved from this activity are the village literacy movement,planting the importance of hand washing for health improvement especially for elementary school students, thegrowing creativity of mothers in utilizing their potential in making products that have economic value, andpreserving dance culture traditional.